Strategies for Building Reputation of Tourism Destinations in Semarang Regency on Social Media - Rizki Halim; Mohammed Aden Suryana; Rachela Belinda Fatharani; Yofiendi Indah Indainanto (Formosa Journal of Social Sciences (FJSS), 2024)
This study aims to analyse the tourism promotion strategy implemented by the Semarang Regency Government through Instagram social media, specifically the @pesona_kabSemarang account. The promotion of attractions through social media is one aspect to support sustainable tourism and increase the number of visitors to the destination. The research method used a qualitative approach by selecting posts based on special features, natural and cultural tourism. The results showed that although there were several promoted events and activities, promotional strategies, there was still a lack of user interaction, such as the number of "likes" and comments. The high tourism potential requires strategic efforts to build reputation and attract tourists to Semarang Regency, especially in optimising social media strategies to increase follower engagement in social media accounts and the effectiveness of tourism destination promotion